Abnormal folate metabolism causes age‐, sex‐ and parent‐of‐origin‐specific haematological defects in mice. (15th August 2018) - Padmanabhan, Nisha; Menelaou, Katerina; Gao, Jiali; Anderson, Alexander; Blake, Georgina E. T.; Li, Tanya; Daw, B. Nuala; Watson, Erica D.
Abstract : Key points: Folate (folic acid) deficiency and mutations in folate‐related genes in humans result in megaloblastic anaemia. Folate metabolism, which requires the enzyme methionine synthase reductase (MTRR), is necessary for DNA synthesis and the transmission of one‐carbon methyl groups for cellular methylation. In this study, we show that the hypomorphic Mtrr gt/gt mutation in mice results in late‐onset and sex‐specific blood defects, including macrocytic anaemia, extramedullary haematopoiesis and lymphopenia. Notably, when either parent carries an Mtrr gt allele, blood phenotypes result in their genetically wildtype adult daughters, the effects of which are parent specific. Our data establish a new model for studying the mechanism of folate metabolism in macrocytic anaemia aetiology and suggest that assessing parental folate status might be important when diagnosing adult patients with unexplained anaemia. Abstract: The importance of the vitamin folate (also known as folic acid) in erythrocyte formation, maturation and/or longevity is apparent since folate deficiency in humans causes megaloblastic anaemia. Megaloblastic anaemia is a type of macrocytic anaemia whereby erythrocytes are enlarged and fewer in number. Folate metabolism is required for thymidine synthesis and one‐carbon metabolism, though its specific role in erythropoiesis is not well understood. Methionine synthase reductase (MTRR) is a key enzyme necessary for the progression of folate metabolism since knocking down the Mtrr gene in mice results in hyperhomocysteinaemia and global DNA hypomethylation. We demonstrate here that abnormal folate metabolism in mice caused by Mtrr gt/gt homozygosity leads to haematopoietic phenotypes that are sex and age dependent. Specifically, Mtrr gt/gt female mice displayed macrocytic anaemia, which might be due to defective erythroid differentiation at the exclusion of haemolysis. This was associated with increased renal Epo mRNA expression, hypercellular bone marrow, and splenic extramedullary haematopoiesis. In contrast, the male response differed since Mtrr gt/gt male mice were not anaemic but did display erythrocytic macrocytosis and lymphopenia. Regardless of sex, these phenotypes were late onset. Remarkably, we also show that when either parent carries an Mtrr gt allele, a haematological defect results in their adult wildtype daughters. However, the specific phenotype was dependent upon the sex of the parent. For instance, wildtype daughters of Mtrr +/gt females displayed normocytic anaemia. In contrast, wildtype daughters of Mtrr +/gt males exhibited erythrocytic microcytosis not associated with anaemia. Therefore, abnormal folate metabolism affects adult haematopoiesis in an age‐, sex‐ and parent‐specific manner. Key points: Folate (folic acid) deficiency and mutations in folate‐related genes in humans result in megaloblastic anaemia. Folate metabolism, which requires the enzyme methionine synthase reductase (MTRR), is necessary for DNA synthesis and the transmission of one‐carbon methyl groups for cellular methylation. In this study, we show that the hypomorphic Mtrr gt/gt mutation in mice results in late‐onset and sex‐specific blood defects, including macrocytic anaemia, extramedullary haematopoiesis and lymphopenia. Notably, when either parent carries an Mtrr gt allele, blood phenotypes result in their genetically wildtype adult daughters, the effects of which are parent specific. Our data establish a new model for studying the mechanism of folate metabolism in macrocytic anaemia aetiology and suggest that assessing parental folate status might be important when diagnosing adult patients with unexplained anaemia.